PENGARUH PENAMBAHAN ABU SEKAM PADI PADA SEMEN PCC TERHADAP MUTU BETON SCC (SELF COMPACTING CONCRETE) - Prasetyo, Tedy; Firdaus, Firdaus (Rang Teknik Journal, 2026)
This study aims to examine the effect of adding rice husk ash (RHA) to Portland Composite Cement (PCC) on the quality of Self-Compacting Concrete (SCC), particularly in terms of compressive strength and split tensile strength. RHA, which is rich in silica, was used as an additive with mixture variations of 0%, 5%, 10%, 15%, and 20%. Experimental methods were applied by producing cylindrical specimens (15 × 30 cm), which were then tested for fresh concrete properties using slump flow and L-box tests, as well as mechanical properties through compressive strength and split tensile strength tests at the ages of 28 and 56 days. The results showed that the addition of RHA improved the performance of SCC. The maximum average compressive strength was 35.90 MPa at 28 days and increased to 38.10 MPa at 56 days. Meanwhile, the maximum average split tensile strength was 3.00 MPa at 28 days and 3.18 MPa at 56 days. These findings suggest that RHA can be used as a supplementary material in PCC to enhance the performance of SCC, although further studies are recommended to determine the optimal proportion and potential combination with other additivesKeywords: rice husk ash, self-compacting concrete (SCC)